A Study on Length-Weight Relationship and Condition Factor of Three Important Freshwater Fish Species of Maijan Beel, Dibrugarh, Assam, India - Singh, Moirangthem Kameshwor; Sonowal, Susmita; Saikia, Chandopal (Asian Journal of Biological and Life Sciences)
The aim of current investigation is to report the length-weight relationship (LWRs) of three economically important as well as ornamental fish species, namely Channa stewartii, Heteropneustes fossilis and Trichogaster fasciata found in Maijan Beel, Dibrugarh, Assam, India. 148 fish specimens belonging to the families Chanidae, Clariidae and Belontiidae were collected and used for the study. The result reported that the exponent ‘b’ in the LWRs (W=aLb) were ranged between 2.61 and 3.00 showing allometric and isometric pattern of growth. The coefficient of correlation (r) recorded in the range of 0.91 to 0.96 and showed high degree correlation in all the species. The Fulton’s condition factor (K) value was varied for each species from 0.53 to 1.79. These parameters are of great important to evaluate the biology, habitat condition, management of the population dynamics and stock assessment of the fishes.
Keywords: Condition factor; Correlation-coefficient; Isometric growth.; Length-weight relationship; Maijan Beel